Reconstructing a Manufacturing Laboratory to a Learning Factory: a TTK UAS Case Study - Tavo Kangru; Madis Moor; Andrei Rudz; Aleksander Jänes (Journal of Machine Engineering)
The rapidly developing manufacturing industry constantly needs top specialists to ensure sustainability (resource optimisation, production efficiency, sustainable products) and to implement the latest know-how (digitalisation, big data analytics, artificial intelligence). Those requirements, in turn, place higher demands on universities, curricula, teaching staff and, above all, laboratories to teach the concept of a smart factory. TTK University of Applied Sciences (TTK UAS) has come to an understanding that renovation of existing production laboratories is unavoidable. Keeping this in mind, a study needs to be conducted to investigate best practices and strategies to develop a new concept that best suits TTK UAS. In this article, the authors examine how to renovate and update the existing university laboratories (production, measurement, CAD/CAM) using simulation software with a Learning Factory concept in mind while still ensuring research development capability. Using the case-study methodology, factory automation simulation software, and a new pedagogical approach, the TTK UAS industrial engineering laboratories are functioning as a cluster, achieving higher learning and R&D efficiency.